2019
DOI: 10.1002/mame.201900195
|View full text |Cite
|
Sign up to set email alerts
|

Dual Cross‐Linked Hydrogels with High Strength, Toughness, and Rapid Self‐Recovery Using Dynamic Metal–Ligand Interactions

Abstract: low density of polymer cross-links. Typical fracture energy of a synthetic hydrogel is about 10 J m −2 , [11] which is orders of magnitude lower than that of cartilage (≈1000 J m −2 ), [12] and natural rubbers (10000 J m −2 ). [13] More often than not, a compromise between high strength and toughness has to be made [14] as they are typically mutually exclusive properties. In recent years, extensive efforts have been directed toward addressing this problem by introducing energy dissipative mechanisms into the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…This result can be attributed to reorganization to a stronger network during the reassociation of Zn 2+ ‐terpy bonds. We [ 17 ] and others [ 30 ] have previously observed similar strengthening of hydrogel networks. Considering that this recovery took place from a residual strain considerably higher than the Fe 2+ ‐based gel after the same resting period (10 min) for both the gels, the self‐recovery for the Zn 2+ gel was more efficient.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This result can be attributed to reorganization to a stronger network during the reassociation of Zn 2+ ‐terpy bonds. We [ 17 ] and others [ 30 ] have previously observed similar strengthening of hydrogel networks. Considering that this recovery took place from a residual strain considerably higher than the Fe 2+ ‐based gel after the same resting period (10 min) for both the gels, the self‐recovery for the Zn 2+ gel was more efficient.…”
Section: Resultssupporting
confidence: 75%
“…In order to enable recovery after the loading–unloading cycle, physical crosslinks acting as sacrificial bonds have been introduced into hydrogels. Along with other physical interactions such as H‐bonding [ 10–12 ] and ionic bonds [ 13 ] , hydrophobic association [ 14 ] and metal‐ligand co‐ordination [ 15–17 ] are promising reversible interactions that can be employed as sacrificial motifs to provide energy dissipation pathways to the hydrogels. Chen et al reported on agar/hydrophobically associated polyacrylamide (PAM) network, which showed tensile strength of 0.267 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the hydrogel recovered the lost mechanical energy and the hysteresis area was slightly higher, as the first loading–unloading cycle of the rested and original hydrogel was compared (Figure F). A similar increase had been noticed previously by our group , and others and suggested the possibility of stronger network formation with better energy-dissipating ability. Similar to tensile force, the extent of recovery was evaluated under the compressive force by subjecting the hydrogel to successive compressive–relaxation cycles.…”
Section: Resultssupporting
confidence: 90%
“…Accordingly, in recent decades, enormous research efforts have been focused on realizing hydrogels suitable for real-world applications that require superior mechanical integrity. Typical strategies explored to achieve this include the formation of double-networks (DNs) , and dynamic cross-linking as well as the incorporation of nanofillers, , metal coordination, macromolecular cross-linking, and dual physical cross-linking. , Several attempts were also made by combining the abovementioned methods. …”
Section: Introductionmentioning
confidence: 99%